1997
DOI: 10.1680/macr.1997.49.178.15
|View full text |Cite
|
Sign up to set email alerts
|

Influence of constituents and composition on autogenous shrinkage of cementitious materials

Abstract: Effects of cement type, water to binder ratio and volume concentration of aggregate on autogenous shrinkage of cement based materials were experimentally investigated. A large amount of autogenous shrinkage was observed in cement paste and concrete with low water to binder ratio. Autogenous shrinkage increased with increasing C3A content of cement. It was also increased by using blast furnace slag with higher fineness. The effect of volunre concentration of aggregate could be estimated by an existing composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
4

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(25 citation statements)
references
References 0 publications
3
18
0
4
Order By: Relevance
“…From Figure 4, it can be seen that the Portland cement CEM I cracks after 30 hours of hardening. This is in good agreement with literature results [3][4][5]. Although the specimens made of Blast furnace slag cements build up a substantial level of tensile stresses, they turned out not to crack with the deformations fully restrained.…”
Section: Results: Paste Measurementssupporting
confidence: 92%
“…From Figure 4, it can be seen that the Portland cement CEM I cracks after 30 hours of hardening. This is in good agreement with literature results [3][4][5]. Although the specimens made of Blast furnace slag cements build up a substantial level of tensile stresses, they turned out not to crack with the deformations fully restrained.…”
Section: Results: Paste Measurementssupporting
confidence: 92%
“…Autogenous shrinkage values of the 16 tested SCC and two HPC mixtures are compared to values predicted from the Tawaza and Miyazawa model 1997 [9], Jonasson and Hedlund model 2000 [10], and CEB-FIP model 1999 [11]. In order to improve the prediction accuracy, the cement type factor of Tazawa and Miyazawa prediction model was modified by applying the test data to the prediction model.…”
Section: Modification Of Existing Autogenous Shrinkage Prediction Modelmentioning
confidence: 99%
“…On the other hand, those of Belite-rich low-heat Portland cement (LPC) were 26%, 55%, 3%, and 9%, respectively. A previous study revealed that the mineral composition of cement affects autogenous shrinkage significantly (Tazawa et al 1993, Tazawa et al 1997. Based on Eq.…”
Section: Methodsmentioning
confidence: 99%